Impact of Milk Drying Methods on Its Nutritional Content and Health Benefits - Yuosra Amer Ali; Azhar ibrahim shuker; Qaswaa Yousif Jameel (University of Thi-Qar Journal of agricultural research, 2025)
The process of milk drying serves two main purposes which include product shelf-life extension and storage stability improvement and dairy product distribution support. The chosen drying technique determines how well the final product will maintain its nutritional value and functional characteristics. The research assesses how three typical milk drying methods (spray drying , freeze drying , drum drying) affect the stability and bioavailability and physical properties of milk components including proteins and lipids and vitamins and minerals.The review examines experimental results from current times to understand how different processing conditions at various temperatures and moisture levels and oxygen exposure times and drying periods affect nutrient breakdown through protein denaturation and lipid oxidation and vitamin depletion, research investigates how hot temperatures lead to damage of heat-sensitive vitamins and bioactive proteins which results in food quality deterioration and negative impacts on human health, also research investigates how industrial efficiency impacts milk powder nutritional preservation because high thermal processing methods used in milk powder production lead to decreased product quality and performance. The research investigates drying systems which employ oxygen-controlled and vacuum-assisted technologies to maintain food nutrient values while meeting safety and quality requirements. The results demonstrate that proper drying methods and new processing methods need to be developed because they will help maintain both the nutritional value and functional properties of dried milk products.